Amiodarone induces cell wall channel formation in yeast Hansenula polymorpha - Kalebina, Tatyana S. (Springerplus, 2015)
The yeast cell wall is constantly remodeled to enable cell growth and division. In this study, we describe a novel type of cell wall modification. We report that the drug amiodarone induces rapid channel formation within the cell wall of the yeast Hansenula polymorpha. Light microscopy shows that shortly after adding amiodarone, spherical structures, which can be stained with DNA binding dyes, form on the cell surface. Electron microphotographs show that amiodarone induces the formation of channels 50–80 nm in diameter in the cell wall that appear to be filled with intracellular material. Using fluorescent microscopy, we demonstrate MitoTracker-positive DNA-containing structures visibly extruded from the cells through these channels. We speculate that the observed channel formation acts to enable the secretion of mitochondrial material from the cell under stressful conditions, thus enabling adaptive changes to the extracellular environment.